The Effect Of Just In Time And Total Quality Management On Environmental Performance Mediated By Green Supply Chain Management (Empirical Studies On Small And Medium Industries In Banda Aceh And Aceh Besar Cities) - Muhammad Adam; maulana ismi saputra (TALENTA Publisher, Universitas Sumatera Utara, 2022)
This study aims to determine the effect of Just In Time and Total Quality Management on Environmental Performance with Green Supply Chain Management as a mediator in Small and Medium Industries in Banda Aceh and Aceh Besar. The sample used in this study was the IKM in the cities of Banda Aceh and Aceh Besar, amounting to 357 respondents. This research method uses a questionnaire as the research instrument. The sampling technique used is purposive sampling. Linear Hierarchical Regression is used as an analytical method to determine the effect of all the variables involved. This study shows that Just In Time and Total Quality Management have an effect on Environmental Performance and Green Supply Chain Management, Green Supply Chain Management has an effect on Environmental Performance and mediates the relationship between Just In Time, Total Quality Management, and Environmental Performance.